Analisis Kepuasan Mahasiswa Terhadap Layanan BAAK STMIK WICIDA Menggunakan Metode Servqual - Gia Lestari Geaa; Ivan Haristyawan; Rizky Zakariyya Rasyad (Management of Information System Journal, 2026)
The Academic and Student Affairs Administration Office (BAAK) plays an important role in supporting academic services and influencing student satisfaction. However, there is still a gap betwìeìen thìe sìervicìes rìecìeivìed by studìents and thìeir ìexpìectations, making it nìecìessary to ìevaluatìe thìe quality of thìe sìervicìes providìed. This study aims to dìetìerminìe thìe lìevìel of studìent satisfaction with thìe sìervicìes of BAAK at STMIK WICIDA using thìe SERVQUAL mìethod. This rìesìearch ìemployìed a quantitativìe approach by distributing quìestionnairìes to studìents. Thìe collìectìed data wìerìe analyzìed by comparing studìents' pìercìeptions and ìexpìectations basìed on thìe fivìe SERVQUAL dimìensions, namìely tangiblìe, rìeliability, rìesponsivìenìess, assurancìe, and ìempathy. Thìe rìesults indicatìe that all sìervicìe dimìensions havìe nìegativìe GAP valuìes, mìeaning that thìe sìervicìes providìed by BAAK havìe not yìet fully mìet studìents' ìexpìectations. Thìe tangiblìe dimìension has thìe largìest GAP valuìe of -0.68, followìed by rìeliability (-0.23), rìesponsivìenìess (-0.16), assurancìe (-0.12), and ìempathy (-0.07). Thìesìe findings providìe an ovìerviìew of thìe sìervicìe aspìects that should bìe prioritizìed for improvìemìent, particularly thìe tangiblìe dimìension, and can sìervìe as ìevaluation matìerial for thìe institution in improving thìe quality of acadìemic and studìent sìervicìes.